2018
DOI: 10.20884/1.oa.2018.14.2.537
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Indigosol Blue 04B Batik Effluent by Indigenous Fungal Isolates, Aspergillus spp.

Abstract: Effluent from the local batik home industry is a serious problem, because the effluent discharge generated is spread in different places. Untreated effluent can cause environmental pollution, such as in groundwater reservoirs,because most is discharged into rivers. The aim of this research was to evaluate the bioremediation potential of indigenous fungi in liquid culture media with Indigosol Blue 04B (IB) batik effluent. The fungi isolates tested were Aspergillus sp. 1, Aspergillus sp. 2 and Aspergillus sp. 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…This is indicated by the small average value of the percentage reduction in TDS obtained. According to Dewi et al (2018b) reported Aspergillus sp. 3 was the best isolate for reducing TDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is indicated by the small average value of the percentage reduction in TDS obtained. According to Dewi et al (2018b) reported Aspergillus sp. 3 was the best isolate for reducing TDS.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal isolate was used in this research was isolate of Aspergillus sp. 3, isolated from batik effluent from previous studies (Dewi et al 2018b). Batik dye effluents used in this study were Indigosol Green, Indigosol Purple, and Naphtol Black.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kassim et al 2018), Aspergillus spp. (Dewi et al 2018a;Dewi et al 2018b), and a bacterial consortium (Muchtasjar et al 2019). Indigenous bacteria isolated from heavy metal contaminated sites had resistance to heavy metal toxicity and could be used for heavy metal removal (Irawati et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Destacandose os fungos filamentosos, que de acordo com Khan e Fulekar (2017) são atrativos para a biorremediação sobretudo pela capacidade de realizar auto peletização. Além disso os fungos são os microrganismos mais eficazes para tratar resíduos têxteis e realizar a descoloração, pois possuem vantagens em relação aos seres unicelulares, pois seus micélios são capazes de dissolver substâncias insolúveis através da síntese de enzimas extracelulares (Dewi et al 2018).…”
Section: Introductionunclassified